Epidemiology of hypertension in Yemen: effects of urbanization and geographical area - Modesti, Pietro Amedeo; Bamoshmoosh, Mohamed; Rapi, Stefano; Massetti, Luciano; Al-Hidabi, Dawood; Al Goshae, Husni (Nature Publishing Group, 2013)
Although globalization can contribute to increased blood pressure by spreading unhealthy behaviors, it also provides powerful means to tackle hypertension. The dissemination of information about and advice on cardiovascular prevention and facilitated contact with health services are valuable resources. To investigate the effects of urbanization, geographical area, and air temperature on hypertension burden and kidney damage, a survey was performed in 2008 with a door-to-door approach among urban and rural adult dwellers of three geographic areas (capital, inland, coast) of Yemen. Subjects (n=10?242) received two visits several days apart to confirm the diagnosis of hypertension. Proteinuria (dipstick test ?+1) was used as a marker of kidney damage. Prevalence rates were weighted to represent the Yemen population aged 15-69 years in 2008. Rates of hypertension and proteinuria progressively increased from the capital (6.4%; 95% confidence level (CI) 5.8-7.0 and 5.1%; 4.4-5.9, respectively), to inland areas (7.9%; 7.0-8.7 and 6.1%; 5.1-7.1), to the coastal area (10.1%; 8.9-11.4 and 8.9%; 7.3-10.4). When compared with urban dwellers, rural dwellers had similar hypertension prevalence (adjusted odds ratios (ORs) 1.03; 95% CI 0.91-1.17) but higher proteinuria rates (adjusted ORs 1.55; 1.31-1.85). Overall, home temperature was associated with a lower hypertension rate (adjusted OR 0.98; 0.96-0.99). This large population study reveals that the highest burden of hypertension and kidney damage is detectable in remote areas of the country.